S-K-nonsingular Modules - Shyaa, Farhan Dakhil; Hadi, Inaam Mohammed Ali (Iraqi Journal of Science, 2021)
In this paper, we introduce a type of modules, namely S-K-nonsingular modules, which is a generalization of K-nonsingular modules. A comprehensive study of these classes of modules is given.